Courageous, Purposeful, and Reflexive: Writing as a Missional and Emergent Task - Taylor, Lynne; Heath, Elaine; Rooms, Nigel; Taylor, Steve (Ecclesial Futures, 2021)
Writing is an essential means of communicating ideas. However, it is also hard work. Most writers learn “on the job” through trial and error and self-reflection. This article advocates seeing writing as a missional and emergent task, a craft undertaken towards a greater good. Two different approaches to writing journal articles and books are described, each calling for courage and reflexivity. The article then provides practical insights on how to press through a sense of being stuck, before offering a step-by-step guide to responding to peer reviewer comments. We hope that this practical article will encourage the craft of writing, providing emerging and established writers with practical suggestions as they seek to place themselves and their ideas in the public arena.